dada a função f cuja lei é: f(x)=4x+9,determine f(-2)
Soluções para a tarefa
Respondido por
1
Resposta:
1
Explicação passo-a-passo:
Você substitui x por -2:
f(x) = 4x + 9
f(-2) = 4*(-2) + 9
f(-2) = -8 + 9
f(-2) = 1
Respondido por
1
Resposta:
. f(- 2) = 1
Explicação passo-a-passo:
.
. f(x) = 4x + 9
.
. f(- 2) = 4 . (- 2) + 9
. = - 8 + 9
. = + 1
.
(Espero ter colaborado)
Usuário anônimo:
Obrigado pela "MR".
Perguntas interessantes
Português,
8 meses atrás
Matemática,
8 meses atrás
Inglês,
10 meses atrás
Espanhol,
10 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Geografia,
1 ano atrás